The Impact of Disappointment in Decision Making: Inter-Individual Differences and Electrical Neuroimaging - Tzieropoulos, Helène; Grave De Peralta, Rolando; Bossaerts, Peter; Gonzalez Andino, Sara L. (Frontiers in Human Neuroscience, 2011)
Disappointment, the emotion experienced when faced to reward prediction errors, considerably impact decision making. Individuals tend to modify their behavior in an often unpredictable way just to avoid experiencing negative emotions. Despite its importance, disappointment remains much less studied than regret and its impact on upcoming decisions largely unexplored. Here, we adapted the Trust Game to effectively elicit, quantify and isolate disappointment by relying on the formal definition provided by Bell’s in economics. We evaluated the effects of experienced disappointment and elation on future cooperation and trust as well as the rationality and utility of the different behavioral and neural mechanisms used to cope with disappointment. All participants in our game trusted less and particularly expected less from unknown opponents as a result of disappointing outcomes in the previous trial but not necessarily after elation indicating that behavioral consequences of positive and negative reward prediction errors are not the same. A large variance in the tolerance to disappointment was observed across subjects, with some participants needing only a small disappointment to impulsively bias their subsequent decisions. As revealed by high-density EEG recordings the most tolerant individuals - who thought twice before making a decision and earned more money – relied on different neural generators to contend with neutral and unexpected outcomes. This study thus provide some support to the idea that different neural systems underlie reflexive and reflective decisions within the same individuals as predicted by the dual-system theory of social judgment and decision making.